The Use of High Frequency Radio on Aircraft Operating in the Uncontrolled Airspace of Sam Ratulangi International Airport Manado - Nafila Timami, Jihan; Rahayu Surtiningtyas , Sri; Saptandari, Yuni (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
High Frequency (HF) radio remains essential for maintaining two-way communication between pilots and air traffic controllers, particularly in uncontrolled airspace beyond the reach of Very High Frequency (VHF) signals. This communication is critical for flight safety, especially for small aircraft operating in remote or transoceanic areas around Sam Ratulangi International Airport, Manado. However, some aircraft are still operating without HF equipment, posing potential hazards to other flights within the responsibility of Ujung Pandang FIC Makassar Sector. This study aims to examine the use of HF radio by aircraft operating in uncontrolled airspace around Sam Ratulangi International Airport and its impact on flight safety and traffic flow. A qualitative research approach was applied, with data collected through field observation, in-depth interviews with Air Traffic Control (ATC) personnel at Perum LPPNPI Manado Branch, and documentation of operational procedures and regulations regarding HF radio usage. The findings indicate that HF radio remains a primary and backup communication tool in areas beyond VHF coverage. The main challenges include poor audio quality and frequent interference. Moreover, some aircraft still lack HF radios, highlighting the need for stricter equipment standards and regulatory socialization to enhance aviation safety in the region.